TRAINING ON APPLIED BEHAVIORAL ANALYSIS (ABA) METHODS IN HANDLING CHILDREN WITH SPECIAL NEEDS FOR TEACHERS OF SD CLUSTER III CIAWI BOGOR SUBDISTRICT - Nurmawati, Nurmawati; Ithriyah, Siti (Devotion : Journal of Research and Community Service, 2022)
This study aims to analyze the applied behavioral analysis training method in dealing with children with special needs. The research method used in this study is a qualitative descriptive method. The type of data used in this study is qualitative data, which is categorized into two types, namely primary data and secondary data. Sources of data obtained through library research techniques (library study) which refers to sources available both online and offline such as: scientific journals, books and news sourced from trusted sources. The results of the study concluded that occupational therapy helps children train the muscles of the body and legs to be strong and balanced right and left. Teach which emphasizes children to be able to work purposefully in their community. Sensory integration therapy teaches children how to train the balance of the right brain and left brain to develop in a balanced way. Sone-rise has the main principle of following "whatever" the child wants to do, there is nothing wrong with the child's behavior and accepting it as it is with passion and love. The therapies above are more focused on physical and minimizing hyper behavior in children, while none has focused on communication skills in children. Therefore we need a comprehensive therapy in helping children's development. A comprehensive therapy in helping children's development is Applied Behavior Analysis (ABA) therapy.